2022
DOI: 10.3390/biology11030417
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic Lymphohistiocytosis Gene Variants in Multisystem Inflammatory Syndrome in Children

Abstract: Multisystem inflammatory syndrome in children (MIS-C) affects few children previously infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In 2020, 45 children admitted to our hospital for MIS-C underwent genetic screening with a commercial 109-immune-gene panel. Thirty-nine children were diagnosed with MIS-C, and 25.4% of the 39 MIS-C patients harbored rare heterozygous missense mutations either in primary hemophagocytic lymphohistiocytosis (pHLH) genes (LYST, STXBP2, PRF1, UNC13D, AP3B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 39 publications
5
58
0
Order By: Relevance
“…Those genes include PRF1 , that we found mutated in 5 patients with MIS-C and previously in 20 patients with autoinflammatory diseases, all bearing the pathogenic Ala91Val mutation that seems to be peculiar to Southern Italy and NOD2 (mutated in two MIS-C patients - one of which compound heterozygous for two different mutations). Our results are in agreement with a recent report documenting HLH associated gene (including DOCK8 and PRF1 ) mutations identified in children with MIS-C ( 34 ). Of interest, one MIS-C patient was heterozygous for three mutations in the MEFV gene.…”
Section: Discussionsupporting
confidence: 94%
“…Those genes include PRF1 , that we found mutated in 5 patients with MIS-C and previously in 20 patients with autoinflammatory diseases, all bearing the pathogenic Ala91Val mutation that seems to be peculiar to Southern Italy and NOD2 (mutated in two MIS-C patients - one of which compound heterozygous for two different mutations). Our results are in agreement with a recent report documenting HLH associated gene (including DOCK8 and PRF1 ) mutations identified in children with MIS-C ( 34 ). Of interest, one MIS-C patient was heterozygous for three mutations in the MEFV gene.…”
Section: Discussionsupporting
confidence: 94%
“…The median age of children affected by MIS-C, clinical features and prevalence of comorbidities are in accordance with those of previously published cohorts (Ahmed et al 2020 ; Feldstein et al 2020 , Lee et al 2020 ; Chou et al 2021 ; Sancho-Shimizu et al 2021 ). However, similar to Vagrecha et al ( 2022 ), we found a clear male preponderance (68.7%) in our MIS-C cohort. The male sex bias is also evident for COVID-19 hospitalization and death, compared to females (The Sex, Gender and COVID-19 Project, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…The STRING v.11.5 database was used to recover the Protein–Protein Interactions (PPIs) of each mutated gene, and Cytoscape software 3.7.1 (Shannon et al 2003 ) was applied to plot the network. Next, the retrieved genes were cross-referenced with those in a dataset of 19 genes, in which variants or abnormal mRNA expression were previously associated with MIS-C (Lee et al 2020 ; Chou et al 2021 ; Beckmann et al 2021 ; Abolhassani et al 2022 ; Vagrecha et al 2022 ) and 14 genes for which genome-wide studies found an association with Kawasaki disease (Sancho-Shimizu et al 2021 ) (Additional file 1 : Table S1). Direct interactions with a confidence score > 0.4 were considered for further enrichment analysis by the web server EnrichR ( https://maayanlab.cloud/Enrichr/ ).…”
Section: Methodsmentioning
confidence: 99%
“…TLR3, IFNB1) were identified among a cohort of MIS-C children from the Middle East [29]. Previously, haploinsufficiency in SOCS1 (suppressor of cytokine signaling 1) was reported in children with MIS-C [30 ]. The same group of investigators also identified a boy with MIS-C possessing a missense mutation in the X-linked gene XIAP & ], a newly proposed HLH gene [18,34 ,35].…”
Section: Key Pointsmentioning
confidence: 99%